Structured Physical Activity did not Affect the Body Fat Percentage among Gymnastics Studio Members - Widiastari, Erina Febriani; Taufik, Fatimah Eliana; Mukhtar, Diniwati (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
The excess of body fat in the body can be associated with the risk of diabetes, cardiovascular disease, and other metabolic diseases. Activities which can reduce the body fat percentage is a structured physical activity. This study aims to identify the effect of the structured physical activity on the decrease in body fat percentage on members of the gymnastics studio. This study used one group of pretest-posttest design. The intervention was an aerobic exercise, conducted for a minimum duration of 150 minutes per week, and followed up for three months. The samples were selected by using purposive sampling andwere collected by measuring the respondent's weight with Bioelectrical Impedance Analysis at the beginning and the end of this study. The data were analyzed by using paired sample t-test. The result showed that the average of the body fat percentage on the pre-test was 33.156 %, and on the post-test was 32.920 %. Based on the data, there was a decrease in a body fat percentage on pre-test and post-test in 13 out of 25 respondents. The p-value was 0.357, and it can be concluded that the structured physical activity did not have a significant effect on the decreasein body fat percentage.